Adaption Of Construction Management Modelling System Through The Use Of Internet Of Things (IoT) - Jaafreh, Ali Bakhit; Al Jaafreh, Mohammad B. (European Scientific Journal, ESJ, 2021)
This paper aims to adapt, implement, and practice the physical use of IoT in the construction management industry as a configuration protocol. The authors describe the general outlines of this field capability as a framework, and they foresaw the opportunities of developing a dominant steam line approach to be incorporated in the construction management side. The challenge is to bond the BMS, SCADA, IoT, smart data “Tags”, green building concepts, smart surveillance, self-moving transportation, and mobile technology in one practical, innovative configuration model. The authors, however, called it “Construction management modelling system” (CMMS). The gap point in this paper is the harnessing of Data Tagging systems along with a smart mobile system via radio frequency and Wi-Fi communication system. The significant effort here is to establish optimum modelling of the IoT system to roll out a product containing all the solutions for the existing and expected obstacles in the construction sites for the different types of projects. The literature review, proposed configuration system, affiliate works, benefits, conclusions, and recommendations have been furnished.